TRANSFORMING TRADITIONAL CLASSROOMS: HARNESSING TECHNOLOGY FOR INCLUSIVE AND ACCESSIBLE EDUCATION - Hasan, Ansarul; Kumar, Anil; Trique, Mohammed (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The classrooms are being transformed with the advent of technology by revolutionizing traditional classroom settings resulting into the creation of valuable opportunities for inclusive and accessible education to all. This paper is an attempt for the exploration of potential role of Educational Technology (EdTech) in the transformation of traditional classrooms into those capable of bridging the learning gaps and promoting such learning environments promoting academic equity. There are so many digital tools, adaptive learning platforms, assistive technologies and AI-based applications that can be integrated for the transformation of traditional classrooms into one, who are in the process of evolution for catering the diverse needs of learners of different nature and background. There are some specific kind of learners also, who are suffering from disabilities and belongs to marginalized communities of the society. For the needs of such learners, this kind of transformation not only enhances the quality of education best suited to them but also capable of fostering an inclusive culture and feeling of global citizenship among them. The present paper is an attempt of judging the suitability of various technological interventions that can be applied for the enhancement of students’ educational engagement, academic achievement and personalized learning. Furthermore the paper addresses the challenges which are usually faced by various stakeholders in implementing the EdTech in educational Institutions of different backgrounds. The findings from the paper highlights that an inclusive and accessible educational environment can be created through the suitable use of technology leading to the adoption of a holistic approach in education.